A tale of the city of Kolkata through the eyes of the “common women" - Santra, Aparajita (Enquiry The ARCC Journal for Architectural Research, 2023)
This paper focuses on working-class women from the informal settlements of Kolkata, India and their precarious relationships with the city. Their existence at the margins of society (socially, spatially, historically, and sometimes even geographically) tends to make them invisible actors in the production of contemporary urban spaces of Kolkata. This paper examines the role of class, caste, and gender in informing the spatial practices of these minoritized women that occur in the city’s liminal landscapes. These practices are quite distinct from those of women from middle- and upper-classes in Kolkata. Terms like “public women” or “bad women” or chhotolok (a common Bengali term used for people from lower classes or castes) have been used to represent and mark these working-class, lower caste women as deviant bodies in terms of their class, caste, and even sexualities. These labels are important to understand how these women have been represented historically in the urban history of Kolkata. By analyzing secondary literature, archival texts, songs, films, poems, and photographs, the paper investigates the following interrelated questions. First, how has the spatial organization of urban Kolkata historically determined the ways in which these women have navigated, engaged with, and attempted to overcome a wide array of structural and systemic constraints? And second, how have these women produced and applied various forms of situated spatial knowledge in the city’s liminal landscapes? In terms of the paper’s structure, I start by analyzing the existing literature on gender and urban space in India. Thereafter, I lay a theoretical groundwork to elucidate the importance of adopting an intersectional lens to understand overlapping regimes of power that affect the life-worlds of minoritized bodies; in this case, the working-class lower caste women of Kolkata. Finally, I use a chronological approach to examine the changes in Kolkata’s urban fabric and its material culture that have significantly added to the precarities faced by these minoritized and marginalized women. In other words, I trace an alternate urban history of Kolkata through the eyes of these “common women.”